Apología al horror cósmico (2020)
The golden object is not of this time, it seems it would be certain that somehow ma managed to travel in the time-space and arriving to our dimension, it is a monster, an alien- gena, but nobody knows nothing of its origin since our knowledge does not have those capabilities